Spectroelectrochemical analysis of HOPG surface controlled modification - Franceschini, Esteban Andrés (2017)
In situ Raman spectroscopy is used to characterize the changes induced by electrochemical oxidation and silver electrodeposition at the step-edge and terrace sites of highly-oriented pyrolytic graphite (HOPG) surfaces. Ag crystallites are observed to become preferentially deposited onto previously oxidized step edges, thereby leading to an enhancement of the Raman active modes of the HOPG surface. Ex situ Raman spectra recorded after HOPG oxidation exhibit clear differences for both terrace and step-edge areas of the surface. An increase of D and D́ band intensity and two well-defined D-band contributions, D1 (at 1324 cm−1) and D2 (at 1344 cm−1), are the main features observed after oxidation. This effect can be correlated with the presence of step-edge sites on the surface, and are found to be strongly dependent on the pH of the solution used in the surface electrochemical oxidation experiments.